Cobertura vacinal e fatores associados em puérperas de município paulista - da Rocha, Bárbara Cristina Casemiro [UNESP]; Carvalheira, Ana Paula Pinho [UNESP]; Ferrari, Anna Paula [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP]; Duarte, Marli Teresinha Cassamassimo [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (FapUNIFESP (SciELO), 2016)
The importance of immunization among actions recommended in the prenatal period raises the possibility of protecting both the mother and the fetus against certain harmful diseases. The scope of this study was to assess the immunization coverage and associated factors of mothers whose deliveries occurred in the first half of 2012 in Botucatu, state of São Paulo. It is a cross-sectional study and data collection was performed in the two municipal maternity hospitals. Of the total births during the study period, 1318 mothers (90.3%) were included The data for the characterization of participants and their vaccination status (diphtheria, tetanus and hepatitis B) were obtained from the prenatal card, hospital records or interviews. For analysis of associated factors, the Chi-square test was used, with a 95% confidence interval and critical p of <0.05. Most of the study participants were 20 years old or more (84.4%), had seven years of schooling (69%), were monitored in prenatal care (99.2%) with seven or more appointments (88.9%). Miscarriage and infant death of 17.7% and 2.4% was recorded, respectively. Vaccination coverage was 68.4%. There was no association between sociodemographic and obstetric variables relating to prenatal care and vaccination of pregnant women.
Immunization coverage and associated factors of women who have recently given birth in a city in São Paulo state
Keywords: Immunization; Immunization coverage; Pregnant women; Prenatal care